Morphological and agronomical evaluation of some Moroccan ecotypes of Bituminaria bituminosa (Tedera) - Shaimi N.; Saidi N.; Kallida R.; Al Faiz C. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Forage pastures and legumes have been widely collected in the past, evaluated and valorised as varieties by many breeders worldwide. Some species where however under investigated, in spite of their potential use in animal feed. Perennial legumes as Bituminaria bituminosa is among the species which require special interest, considering their good forage quality and their ability to tolerate drought. Ten ecotypes of Bituminaria bituuminosa, collected from different areas of Morocco mainly Middle Atlas, High Atlas and the Rif, were evaluated for two years under field conditions for the following morphological and agronomical traits: flowering date, plant height (cm), leaf number, stem number, seed length and width, head number, flower number/head, leaflet with (cm), leaflet length (cm), color of flowers, branch number, mean stem diameter (mm), thousand seed weight (g), dry matter yield (g/plant) and grain yield (g/plant). An interesting genetic variability among studied ecotypes was found. In fact, the differences for all measured traits was highly significant (P<0.001) among ecotypes. In terms of dry matter production potential, some ecotypes were very promising. Further investigation should be made to include more ecotypes from other regions of the country.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)